A Systematic Review of Full-Shift, Noise Exposure Levels Among Construction Workers: Are We Improving?. Issue 7 (3rd July 2018) - Lewkowski, Kate; Li, Ian W; Fritschi, Lin; Williams, Warwick; Heyworth, Jane S
Abstract: Context: Construction industry workers are at high risk of occupational noise exposure. Although regulations and guidelines for this industry specify the use of noise controls, workers continue to be exposed to hazardous noise levels. Objectives: The objectives of this study were (i) to collate and describe full-shift noise exposure experienced by construction workers; (ii) to review trends in full-shift exposure over time and between countries; and (iii) to identify any occupational categories within the construction industries that have higher levels of exposure. Results: Of the 1171 studies found using key terms, 25 contained noise exposure measurements that met our inclusion criteria. Sample populations were predominantly from large construction sites and primarily comprised occupations known to engage in noisy workplace activities. Studies spanned over 36 years with all having average full-shift noise exposure over 85 A-weighted decibels (dBA). No time trend in full-shift noise exposure levels for construction workers was observed. Construction workers in the subgroup occupations of mason, sheet metal workers, carpenters, concrete workers, and operating engineers consistently had mean LAeq, 8h over the 85 dBA limit. Conclusion: Studies spanning 36 years in 10 countries consistently show construction workers have been exposed to hazardous noise levels. There has been no significant change over time of the average full-shift exposure levels of construction workers, including in all occupational subgroups except iron-workers. Some variability in full-shift measures is due to sampling methods and population characteristics and to a lesser extent, methods used to derive exposure levels.